A tale of two rings. (20th May 2014) - Prasad, Deepa; Bansal, Manish; Ashwath, Ravi C.
Abstract We describe a rare case of double vascular ring diagnosed with cardiac magnetic resonance imaging in a patient with ventricular septal defect, pulmonary stenosis, and right aortic arch.